Synthesis, Identification and Biological Activity Study of Some New Spiro-Isatin Derivatives - Faisal, Farah N.; Dawood, Rafid S. (Iraqi Journal of Science, 2024)
Spiro-isatin derivatives have been the subject of extensive research due to their diverse pharmacological properties and potential therapeutic applications. These molecules are characterized by a spirocyclic structure that includes an isatin moiety and one or more heterocyclic rings, resulting in a unique and versatile molecular architecture. In this work, a series of new spiro-isatin derivatives B1-12 were synthesized over two steps. The first step included a condensation reaction between isatin and various aromatic amines, affording the corresponding Schiff bases A1-12 in high yields (up to 96%). In the second step, A1-12 underwent a reaction with glycine, resulting in the formation of B1-12 with yields varying between 65 and 92%. The structures of the compounds were confirmed by FT-IR and 1H NMR spectroscopy. A few of the produced compounds were examined for antibacterial and antioxidant properties.